Bibliometric Analysis: Development of Community Based Tourism (CBT) - Based Educational Tourism in the Scopus Database (2014-2025) - Sugeng Handoko (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2026)
Purpose: This research aims to analyze the trends, intellectual structure and dynamics of the development of CBT-based educational tourism studies through a bibliometric analysis approach. Method: Data analysis was carried out using a bibliometric analysis approach by searching Use the